Rancang Bangun Sistem Informasi Penilaian Kienrja Karyawan Pada Program Pemerintah Kota Tanpa Kumuh (KOTAKU) Berbasis Web - Irawan, Yogi; Tjandrarini, A.B; Rahmawati, Endra (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2019)
This research is motivated by problems faced by the Slum City Government Program (Kotaku) in evaluating employee performance. The first problem is often the inaccuracy in distributing employee performance appraisal documents, the second problem is the amount of paper used in conducting one employee performance appraisal, the third problem is the difficulty in filing and searching documents on employee performance evaluation results. Then built a web-based application to be more efficient in supporting the distribution process, reduce costs for paper use and facilitate archiving and search results of employee performance appraisals. In addition, web-based applications do not need to be installed on every computer or laptop. Then this application will be supported by a performance appraisal method that has been implemented by the Kotaku which refers to the Work Order Letter (SPK) Guidelines. Based on the results of the trials that have been carried out, the application of employee performance appraisal on city government programs without slum (my city) makes it easy to evaluate employee performance which previously takes almost 1 week now is only 2 days, this is due to the employee performance assessment system website.Keywords: Assessment, Performance, City, Website